Preparation method and characterization of inclusion complex of Theophylline/Beta / Marina Mokhtar and Rohana Adnan - Mokhtar, Marina; Adnan, Rohana (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Theophylline is a therapy for respiratory diseases which has limited use due to its rapid absorption and becomes inactive metabolite as methyluric acid when administered in the body system. These limitations can be reduced by complexation with inclusion of the beta cyclodextrin. The complex was prepared by kneading, slow evaporation and freeze drying methods. The structure of the complex was determined by FT-IR, DSC and 1H NMR. The molecular modeling study indicated theophylline lies exactly in the cavity of β-CD with hydrogen bonding.